PERANCANGAN PUSAT WISATA KULINER LAUT DI KALIANDA, LAMPUNG SELATAN - Yelva Adprila; Putri Suryandari; Harfa Iskandaria (MAESTRO, 2020)
The Marine Culinary Tourism Center is an architectural design work, with the application of Language Analogy or Linguistic Architecture with the application of a direct ty semiotic model as the chosen design theme, with the hope that it can provide an interpretation of architecture which states that a building is a sign of conveying information about what it really is and what it does in its planning. Kalianda City, South Lampung as the selected location which is a tourism area that has natural and cultural potential typical. The potential and development of the Culinary Tourism Area in Kalianda, South Lampung is actually based on tourism activities which are a socio-cultural interaction, which is related to what consumers or tourists enjoy in tourism activities. Such as the use of natural resources in the form of fishery products and their processing can be used as the main product of tourism.